An Information System Design Product Theory for Student Academic Self-Service University Management System - Muhamad Idaham, Umar Ong; M. A., Ameedeen (Faculty of Computing, College of Computing and Applied Sciences Universiti Malaysia Pahang, 2021)
The role of Information System Design Theory in software development is enormous. With the help of design theory, developers could estimate how the system will be and the reasons why the system reacts that way. The focus of the article is to revised and re-establish the design theory of a self-service university management system. The objectives of this publication are to identify the most relevant publication that will act as a guideline to generate the design theory artifacts and to establish the artifacts which will consist of three components named kernel theory, meta-requirements, and meta-design for the stated system. The system scope will be focused on enabling self-service functions. Validation will be done through FEDS framework with the inclusion of a traceability matrix between the meta-requirement against the real-world user requirement. The significance of this article is to provide an initial set of design theory artifacts to be utilized by software developers in the development or evaluation of a University Management System.